How to develop entrepreneurial graduates, ideas and ventures : designing an imaginative entrepreneurship program - Penaluna, Kath; Jones, Colin; Penaluna, Andy (How to guides, 2022)
"Charged with developing learning, teaching and assessment practices that go beyond delivering discipline-specific subject knowledge, the demands on entrepreneurial educators have increased in recent decades. This guide will help educators develop more entrepreneurial graduates by demonstrating how they can equip learners with key competencies such as team working, creativity, problem solving, and opportunity recognition. This engaging How to Guide shares the journeys of educators working within different contexts to help the reader design an imaginative entrepreneurship program. Providing critical perspectives and observations that are both forward-looking and practice-led, each chapter offers a wide range of insights into the unique practices of some of the world's leading educators in entrepreneurship, education and creativity. With a focus on the development of students and their ventures, educators at any level or discipline within higher education are invited to reflect upon and advance their own practices. Illustrating a vast range of contemporary practices in the field of entrepreneurial education, this compelling book will be an essential tool for any educator whose teaching incorporates entrepreneurship, enterprise and creativity"--